2017
DOI: 10.1371/journal.pone.0173696
|View full text |Cite
|
Sign up to set email alerts
|

Novel copy number variation of the TGFβ3 gene is associated with TGFβ3 gene expression and duration of fertility traits in hens

Abstract: Improvements in the duration of fertility (DF) could increase the interval between successive artificial inseminations, thereby decreasing the cost associated with production of hatching eggs. The molecular mechanisms involved in DF in hens remains under-explored. In this study, expression levels of the transforming growth factor-β genes (TGFβs: TGFβ1, TGFβ2, TGFβ3) were investigated in utero-vaginal junctions (UVJs) of hens with long DF (Group L, n = 10) and short DF (Group S, n = 10). TGFβ1 and 2 tended to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Additionally, immune system activity has been implicated in maintaining sperm storage within the SST and at the time of fertilization 15,16 . Likewise, breeder and co-workers proposed that energy derived from mitochondrial fatty acid oxidation might be important for sperm longevity, motility, mobility and storage in the oviduct.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, immune system activity has been implicated in maintaining sperm storage within the SST and at the time of fertilization 15,16 . Likewise, breeder and co-workers proposed that energy derived from mitochondrial fatty acid oxidation might be important for sperm longevity, motility, mobility and storage in the oviduct.…”
Section: Introductionmentioning
confidence: 99%
“…Two duration of fertility traits DN and FN were measured in terms (DN = the number of days post-insemination until the last fertile egg was produced; and FN = the number of fertile eggs were produced after a single AI). DN and FN were expressed as average of three measurements 8 .…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was isolated using Trizol reagent (Invitrogen, Foster City, CA, USA), following the recommended manufacturers protocol. The quality and quantity of RNA samples were detected by 1.0% agarose gel electrophoresis and absorbance optical density (OD) at a 260/280 nm ratio, respectively 8 . Pair-end 150-bp reads were generated on a Hiseq 2500 sequencing machine at the Shanghai biotechnology corporation.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, CNVs of the genes are associated with reproduction and milk phenotype in cattle (Durán Aguilar et al, 2017;Da Silva et al, 2016b;McCarthy et al, 2012;Prinsen et al, 2017;Sermyagin et al, 2016;Shin et al, 2014;Xu et al, 2016;Yue et al, 2013;Zhou et al, 2018). In chickens, novel CNV of the TGFβ3 gene is associated with duration of fertility traits (Gu et al, 2017). The study of Sasaki et al (2016) identified a deleted-type CNV encompassing ANXA10 in cows that was associated with embryonic mortality at 30-60 days after artificial insemination.…”
Section: Association Of Cnvs With Reproduction and Production Traitsmentioning
confidence: 99%